Humanize the training of pedagogy students : An analysis in times of pandemic - Infante-Malachias, María Elena; Guevara, Juan Luis; Araya-Crisóstomo, Sandra (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The difficulties reported by pedagogy students from two Latin American universities are analyzed in the context of the COVID-19 pandemic. Written records and surveys answered by the students all were analyzed from a Freirean vision of education. The results show how the distancing of teachers, students and their peers caused various pedagogical difficulties, and were worsened by the emotional suffering of the young people, affected negatively their training processes. The educational practice that values dialogue and the contexts of interests and motivations of the students becomes fundamental for their academic training to be made more human, integrated and transdisciplinary.